Tendensi Asal Sarang Penyu yang Direlokasi ke Pusat Pendidikan dan Konservasi Penyu, Serangan-Bali - Parawangsa, I Nyoman Yoga; Sukanta, I Made; Budi, Eka Saktiawan; Utami, Dhita Hardiyanti (Jurnal Sumberdaya Akuatik Indopasifik, 2024)
Sea turtles are one of the living fossils that still exist. There are only 7 species of sea turtles in the world. Sea turtles have encountered many threats, even since they were still in the egg on the nesting beach. The nest of turtle eggs on the beach have some threats like predators, theft, sabrasion and coastline changes that increase the action of relocation of turtle nests are needed to save the eggs. Ths study aimed to know the estendency of native places from the eggs which are relocated to semi-natural nests at Turtle Conservation and Education Center, Serangan-Bali. The data was collected from 2015 until 2019. In 5 years the number of nest rescued was 792 and the number of eggwas 87.303. The nest which relocated to semi-natural nest in TCEC came from 27 nesting habitats. Mostly the nest native to Klungkung beach, Serangan beach, and Lembeng beach with the number of turtle eggs on each beach were 211 nests, 179 nests, and 174 nests.